Protective and risk factors associated with comorbid mental health disorders and psychological distress among Latinx subgroups. - Barragán, Armando; Yamada, Ann-Marie; Gilreath, Tamika D.; Lizano, Erica L. (Journal of Human Behavior in the Social Environment, 2020)
Psychological distress, often coupled with comorbid mental illnesses, affects Latinxs at higher rates and severity than other ethnic groups. This study examined differences in the association between comorbid mental illnesses and psychological distress between Latinx subgroups. Using a sample of 28,630 adults from the National Health Interview Survey, this study used hierarchical multiple regression models to test for differences in psychological distress among various Latinx subgroups and interactions effects between Latinx subgroups and psychological distress. The presence of multiple mental health disorders and comorbid mental health disorders were associated with greater rates of psychological distress. The relationship between mental health disorders and psychological distress varied by Latinx subgroup. An interaction test yielded a significant interaction between being Puerto Rican and having no mental health disorders. Puerto Ricans with no mental health disorders report higher rates of psychological distress when compared to other Latinx subgroups. The implications of the study findings for mental health services for Latinx groups and for future research are discussed.